ORAL ALLERGY SYNDROME AND DENTAL ALLERGOLOGY. - Miglena Balcheva; Assya Krasteva; Georgi Nikolov; Martin Georgiev; Rumiana Hristova; Mariela Hristova; Yana Kandova; Iliana Stoeva; Angelina Kisselova-Yaneva; Bogdan Petrunov; Maria Dencheva; Mariana Tsekova (Peytchinski Publishing, 2013)
The reactivity to food proteins is specific, but in certain patients cross reactions are observed between food proteins of plant or animal origin and non-food ones. The most common clinical manifestation of this cross reactivity is oral allergy syndrome (OAS). It develops mainly in patients with pollen allergy after fresh fruit and vegetables consumption. The symptoms are oro-pharyngeal pruritus, papules and vesicles which resemble mouth ulcers on the labial mucosa and labial, palatal and lingual swelling. There may also be a sensation of pharyngeal swelling. The symptoms appear very quickly and may be followed by urticaria or contiguous facial erythema. The progress of this syndrome is due to homology of structural proteins in foods of plant origin and in pollens.